Supplementary Light Differently Influences Physico-Chemical Parameters and Antioxidant Compounds of Tomato Fruits Hybrids - Onofrio Davide Palmitessa; Miriana Durante; Sofia Caretto; Francesco Milano; Massimiliano D'Imperio; Francesco Serio; Pietro Santamaria (Antioxidants, 2021)
One of the challenges for agriculture in the coming years will be producing more food avoiding reducing the nutritional values of fruits and vegetables, sources of nutraceutical compounds. It has been demonstrated that light-emitting diodes (LEDs) used as a supplementary light (SL) technology improve tomato yield in Mediterranean greenhouses, but few data have been reported about SL effects on fruit physio-chemical parameters. In this study, three tomato hybrid (F1) cultivars were grown for year-round production in a commercial semi-closed glasshouse in Southern Italy: red cherry type (“Sorentyno”), red plum type (“Solarino”), and yellow plum type (“Maggino”). From 120 to 243 days after transplant (DAT), Red/White/Blue LEDs were used as SL. The fruits harvested 180 DAT were analyzed and those obtained under LEDs had 3% more dry weight, 15% more total soluble solids, and 16% higher titratable acidity than fruits grown only under natural light. Generally, the antioxidant activity and the mineral profile of the fruits were not negatively influenced by SL. Lycopene content was unchanged and vitamin C content of “Sorentyno” even increased by 15% under LEDs. Overall, LEDs used as SL technology could be one of the tools used by agriculture in Mediterranean basin to produce more food maintaining high quality production.